What happens to education during a pandemic? Evidence from a Colombian case (2021)
In this paper we show the results of an investigation into changes in the performance of EAFIT University students during the two semesters of 2020 compared with statistically similar cohorts from 2019. We used the Differencein-Difference method and find that student performance during emergency virtual education was around 0.2 decimals better than in previous periods, it was measured according to the obtained grade. These results are consistent even when classified by geographical location, economic background, and the discipline the student is enrolled in. To better understand the mechanism that caused this change, we discuss the results using semi structured interviews carried out with teachers, and analysis on student perception surveys performed by the institution. The results suggest that this change could be explained by student abilities, successful actions taken by the institution and increase in collaborative testing methodologies.